Analysis of ground thermal control systems for solar photovoltaic performance enhancement - Reda, M.N. (WITPress, 2020)
Arid areas are characterized by high solar radiation, which is an advantage for the performance of photovoltaic (PV) panels. However, they are deteriorating by two setbacks from the harsh climate: shallow temperatures during the night, leading to condensation and overheating during the day, leading to reduced efficiency. The paper discusses and resolves the two setbacks in the performance by cooling the panel during the day and heating it during the night using a ground embedded heat exchanger. Experimental and numerical methods are adopted to carry out the investigation. For that, a numerical model was developed and subjected to a series of measurements. Two PV modules have been tested simultaneously; one is with thermal control system and the second without thermal control. A reduction in the PV surface temperature by around 8°C can be obtained during the daytime. The same system can rise the PV surface temperature by around 3°C more than the temperature at which condensation takes place. © 2020 WIT Press.